Crystal, electronic and magnetic structures of a novel series of intergrowth carbometalates R4Co2C3 (R = Y, Gd, Tb). Issue 12 (8th March 2021) - Levytskyi, Volodymyr; Isnard, Olivier; Kremer, Reinhard K.; Babizhetskyy, Volodymyr; Fontaine, Bruno; Rocquefelte, Xavier; Halet, Jean-François; Gumeniuk, Roman
Abstract : R4 Co2 C3 (R = Gd, Tb) carbides are magnetic metals and their crystal structures result from the stacking of alternating RCoC (YCoC-type) and R2 C ( anti -CdCl2 type) fragments with a 2 : 1 ratio. Abstract : A series of new ternary isostructural R4 Co2 C3 (R = Y, Gd, Tb) carbides was synthesized by annealing of arc-melted stoichiometric samples. The crystal structure of Tb4 Co2 C3 [space group P 2/ m, Pearson symbol mP 18, a = 12.754(2) Å, b = 3.6251(4) Å, c = 7.0731(9) Å, β = 105.601(6)°] was solved by direct methods from neutron powder diffraction data collected at 100 K. The room temperature unit cell parameters of the new phases were determined by X-ray powder diffraction technique. The crystal structure of Tb4 Co2 C3 is characterized as an intergrowth structure resulting from the stacking of alternating TbCoC (YCoC-type) and Tb2 C ( anti -CdCl2 type) fragments with a 2 : 1 ratio. Tb4 Co2 C3 orders ferromagnetically at T C = 35(1) K, whereas the isostructural Gd4 Co2 C3 reveals two magnetic transitions at T C1 = 82(3) K and T C2 = 13(2) K. Density functional theory (DFT) calculations confirm that the magnetic moments of the R4 Co2 C3 (R = Gd, Tb) carbides are exclusively due to the rare-earth elements. Y4 Co2 C3 is shown to be a Pauli-paramagnet by experimental and theoretical studies.